Progressive immediate loading of a perforated maxillary sinus dental implant: a case report - Al-Juboori MJ (Dove Medical Press, 2015)
Mohammed Jasim Al-Juboori Department of Oral Surgery, MAHSA University, Kuala Lumpur, Malaysia Abstract: The displacement of a dental implant into the maxillary sinus may lead to implant failure due to exposure of the apical third or the tip of the implant beyond the bone, resulting in soft tissue growth. This case report discusses dental implant placement in the upper first molar area with maxillary sinus involvement of approximately 2 mm. A new technique for progressive implant loading was used, involving immediately loaded implants with maxillary sinus perforation and low primary stability. Follow-up was performed with resonance frequency analysis and compared with an implant placed adjacent in the upper second premolar area using a conventional delayed loading protocol. Implants with maxillary sinus involvement showed increasing stability during the healing period. We found that progressive implant loading may be a safe technique for the placement of immediately loaded implants with maxillary sinus involvement. Keywords: progressive implant loading, resonance frequency analysis, implant stability, provisional crown, bone density, maxillary sinus